Accuracy of breath tests using low doses of 13C-urea to diagnose Helicobacter pylori infection: a randomised controlled trial. Issue 4 (14th September 2005) - Gatta, L; Ricci, C; Tampieri, A; Osborn, J; Perna, F; Bernabucci, V; Vaira, D
Abstract : Background: The 13 C-urea breath test (UBT) for detecting Helicobacter pylori infection is a non-invasive method based on the organism's urease activity. Since its first description, the method has been extensively modified. However, only the dose of 13 C-urea and the measurement equipment are directly related to the cost of the test. Aims: (1) To assess the diagnostic accuracy before eradication therapy of three UBTs using 25, 15, and 10 mg of 13 C-urea, respectively; and (2) to determine diagnostic performance in the post-eradication setting showing the highest values for sensitivity and specificity with the lowest dose of 13 C-urea. Methods: Three hundred consecutive patients were randomised to be tested with one of the three UBTs. All patients underwent upper endoscopy with biopsies. A total of 222 more patients were enrolled to evaluate the second aim. Infected patients were offered treatment and asked to return 4–6 weeks after the end of therapy to perform endoscopic follow up and to carry out 13 C-UBT. Results: In the pretreatment setting, 13 C-UBT 25 mg had a sensitivity of 100% (95% confidence interval (CI) 91.8–100) and a specificity of 100% (95% CI 93.7–100); 13 C-UBT 15 mg had a sensitivity of 96.1% (95% CI 86.8–98.9) and a specificity of 100% (95% CI 92.6–100); and 13 C-UBT 10 mg had a sensitivity of 89.1% (95% CI 77–95.3) and a specificity of 100% (95% CI 93.3–100). As the test with the best performance and the lowest dose of 13 C-urea was 13 C-UBT 15 mg, it was evaluated after treatment, reporting a sensitivity of 100% (95% CI 79.6–100) and a specificity of 98.9% (95% CI 94.3–99.8). Discussion: UBTs using 25 and 15 mg of 13 C-urea were both accurate in the diagnosis of H pylori infection in untreated patients. 13 C-UBT 15 mg was also accurate for follow up of patients after treatment.